Optimization of understanding and learning outcomes in arabic through the congruence evaluation model approach for sd al-amin sukoharjo students - Dudi Budi Astoko; Muhammad Isa Anshory; Achmad Rosyid Ridha; Muhammad Budi Sumarwan; Isa Faizul Haq (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to examine the effectiveness of the Congruence Evaluation Model in optimizing students’ comprehension and learning outcomes in Arabic language instruction at SD Al-Amin Sukoharjo. The research questions addressed are: (1) How is Arabic language learning implemented based on the Congruence Evaluation Model? (2) To what extent does this model influence students’ conceptual understanding and academic achievement? A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group. The population consisted of fifth-grade students at SD Al-Amin Sukoharjo, with purposive sampling applied to select the participants. Research instruments included validated tests on Arabic comprehension and learning outcomes. Data were analyzed using t-tests and gain score analysis. The results reveal a significant difference between the experimental and control groups, indicating that students who received instruction through the Congruence Evaluation Model demonstrated greater improvements in both comprehension and academic performance. These findings suggest that the alignment between instructional objectives, processes, and outcomes—core to the Congruence Evaluation Model—enhances the effectiveness of Arabic language learning at the elementary level. This study recommends the integration of the Congruence Evaluation Model as a strategic alternative for formative and reflective assessment-based learning.